Tough electromagnetic interference shielding hydrogel material as well as preparation method and application thereof

By introducing MXene and salting treatment into the hydrogel, a dual network structure is constructed, which solves the problem of insufficient mechanical and conductive properties of existing hydrogel materials, and the preparation of strong electromagnetic interference shielding hydrogel materials is realized, with excellent mechanical and electromagnetic shielding properties.

CN119708361AInactive Publication Date: 2025-03-28UNIV OF SCI & TECH OF CHINA

Patent Information

Application Number
CN202510213787.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

While maintaining high-efficiency EMI shielding performance, existing hydrogel electromagnetic shielding materials have weak mechanical properties and low electrical conductivity, which limits their application in flexible electronic devices and EMI shielding.

Method used

By mixing chitosan, acrylic, crosslinking agent, thermal initiator and MXene dispersion, ultrasonic dispersion treatment and vacuum degassing, followed by thermal polymerization and salting treatment, a strong electromagnetic interference shielding hydrogel material was prepared.

Benefits of technology

This method constructs a dual network structure, significantly improving the mechanical properties and conductive properties of the hydrogel, and achieving excellent mechanical properties, electromagnetic shielding properties and electrical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708361A_ABST
    Figure CN119708361A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of intelligent soft materials, and particularly relates to a tough electromagnetic interference shielding hydrogel material and a preparation method and application thereof.The preparation method comprises the following steps that S1, chitosan, acrylic acid, a cross-linking agent, a thermal initiator and MXene dispersion liquid are added into water, and a mixed solution is obtained; s2, carrying out ultrasonic dispersion treatment on the mixed solution, uniformly mixing in a vacuum environment, and degassing to obtain a reaction solution; s3, heating the reaction liquid to enable acrylic acid in the reaction liquid to be subjected to thermal polymerization to generate MXene / polyacrylic acid-chitosan composite hydrogel; through construction of a double-network structure and salting-out treatment, the mechanical property of the hydrogel is greatly improved, so that the hydrogel has relatively high strength and fracture toughness; a proper amount of MXene is added and salting-out treatment is carried out, so that the conductivity and electromagnetic interference shielding performance of the hydrogel are improved, and the prepared hydrogel has excellent mechanical property, electromagnetic shielding performance and electrical (strain sensing) performance and has an obvious and good resistance-strain effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of intelligent soft materials, and in particular to a strong electromagnetic interference shielding hydrogel material and a preparation method and application thereof. Background Art

[0002] Hydrogels are composite materials composed of a large amount of water and a three-dimensional polymer network. The abundant water molecules in hydrogels can cause strong absorption attenuation, polarization, and dielectric loss of electromagnetic signals in the gigahertz and terahertz frequency bands. And due to their porous structure, hydrogels show obvious advantages in high-performance EMI shielding applications. In recent years, researchers have developed several methods to incorporate conductive fillers into hydrogel matrices, such as metal-based fillers, carbon nanotubes or nanofibers, and two-dimensional nanomaterials MXenes, to improve their EMI shielding performance.

[0003] However, these hydrogel shielding materials usually have weak mechanical properties (low strength and fracture toughness, and the stretchability of the gel also needs to be further improved) and low conductivity (materials with good conductivity generally have better shielding properties), which limits their application in flexible electronic devices and EMI shielding; therefore, achieving excellent mechanical properties while maintaining efficient EMI shielding performance remains a key issue and challenge in the current research and development of hydrogel electromagnetic shielding materials. Summary of the invention

[0004] In order to make up for the deficiencies of the prior art, the purpose of the present invention is to provide a strong electromagnetic interference shielding hydrogel material and a preparation method and application thereof.

[0005] The technical solution adopted by the present invention to solve the technical problem is: a strong electromagnetic interference shielding hydrogel material and a preparation method and application thereof described in the present invention include the following steps: S1: adding chitosan, acrylic acid, crosslinking agent, thermal initiator and MXene dispersion into water to obtain a mixed solution; S2: subjecting the mixed solution to ultrasonic dispersion treatment, and then mixing it evenly in a vacuum environment and degassing it to obtain a reaction solution; S3: heating the reaction solution to thermally polymerize the acrylic acid therein to generate a MXene / polyacrylic acid-chitosan composite hydrogel; S4: The composite hydrogel is immersed in an ammonium sulfate solution for salting out to obtain a strong electromagnetic interference shielding hydrogel material.

[0006] Preferably, the mass ratio of chitosan, acrylic acid, MXene dispersion and water in S1 is (0.2-0.6):3:(1.5-4.5):(5.5-2.5).

[0007] Preferably, the cross-linking agent in S1 is N,N'-methylenebis(acrylamide), and the thermal initiator is 2,2'-azobis(2-methylpropionamidine) dihydrochloride.

[0008] Preferably, the concentration of the MXene dispersion is 20 mg / mL, and the flake size of the MXene is between 200 and 500 nm.

[0009] Preferably, the heating temperature in S3 is 50° C. to 65° C., and the heating time is 3 to 10 hours.

[0010] Preferably, the concentration of the ammonium sulfate solution in S4 is 15%-43%, and the mass ratio of the ammonium sulfate solution to the MXene / polyacrylic acid-chitosan composite hydrogel is (200-1000):10.

[0011] Preferably, the temperature of the ammonium sulfate in S4 is 0°C to 30°C; and the salting-out time is 48h to 72h.

[0012] A strong and tough electromagnetic interference shielding hydrogel material is prepared by any one of the preparation methods for a strong and tough electromagnetic interference shielding hydrogel material.

[0013] A strong and tough electromagnetic interference shielding hydrogel material is used to prepare flexible electromagnetic shielding devices and flexible sensors.

[0014] The beneficial effects of the present invention are as follows: 1. The tough electromagnetic interference shielding hydrogel material and its preparation method and application described in the present invention greatly improve the mechanical properties of the hydrogel by constructing a double network structure and subjecting the hydrogel to salting-out treatment, and especially make the hydrogel have higher strength and fracture toughness; in addition, the present invention significantly improves the conductive properties and electromagnetic interference shielding properties of the hydrogel by adding an appropriate amount of MXene and salting-out.

[0015] 2. A strong and tough electromagnetic interference shielding hydrogel material and its preparation method and application described in the present invention. The hydrogel prepared by the present invention has excellent mechanical properties, electromagnetic shielding properties and electrical (strain sensing) properties. At the same time, the hydrogel prepared by the present invention has an obvious and good electrical property of resistance-strain effect; the hydrogel prepared by the present invention has excellent mechanical properties, electromagnetic interference shielding properties and electrical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The present invention will be further described below in conjunction with the accompanying drawings.

[0017] Figure 1 This is the preparation process of the electromagnetic interference shielding hydrogel in this article; Figure 2The stress-strain curve test results of the hydrogels prepared in the comparative examples and embodiments of the present invention; Figure 2 (a) is the stress-strain curve of the hydrogel prepared in Comparative Example 1 of the present invention; Figure 2 (b) is the stress-strain curve of the hydrogel prepared in Example 1 of the present invention; Figure 2 (c) is the stress-strain curve of the hydrogel prepared in Example 2 of the present invention; Figure 2 (d) is the stress-strain curve of the hydrogel prepared in Example 3 of the present invention; Figure 2 (e) is the stress-strain curve of the hydrogel prepared in Comparative Example 2 of the present invention; Figure 2 (f) is the stress-strain curve of the hydrogel prepared in Example 4 of the present invention; Figure 2 (g) is the stress-strain curve of the hydrogel prepared in Example 5 of the present invention; Figure 3 The relative resistance change-strain curve test result of the hydrogel prepared in Example 4 of the present invention; Figure 4 The electromagnetic shielding effect of the hydrogels prepared in the comparative example and the examples of the present invention is compared; Figure 4 (a) is a comparison of the electromagnetic interference shielding effect (EMI SE) of the hydrogels prepared in Comparative Example 2, Example 5, Example 4 and Example 1 of the present invention; Figure 4 (b) is a comparison of the electromagnetic interference shielding effect (EMI SE) of the hydrogels prepared in Comparative Example 4, Comparative Example 3, Example 7, Example 6 and Example 1 of the present invention. DETAILED DESCRIPTION

[0018] The present invention is further described below in conjunction with the embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0019] In addition, the preparation processes in the following examples are all conventional means in the prior art unless otherwise specified, and therefore, they are not described in detail; the raw materials used in the following experiments are all commercially available products unless otherwise specified.

[0020] Comparative Example 1 S1: 0.6 g chitosan, 3 g acrylic acid, 2.5 mg N, N'-methylenebis(acrylamide), 10.87 mg 2,2'-azobis(2-methylpropionamidine) dihydrochloride, and 4.5 g MXene dispersion were added to 2.5 g deionized water and stirred to form a mixed solution; S2: The mixed solution was first subjected to ultrasonic treatment for 30 minutes and then vacuum stirred for 10 minutes to mix and degas; S3: injecting it into a mold consisting of two glass plates separated by a 1 mm silicone gasket; placing the mold in a constant temperature box at 50°C to allow acrylic acid to undergo free radical polymerization for 6 hours to generate a MXene polyacrylic acid-chitosan composite hydrogel; S4: At room temperature, the MXene / polyacrylic acid-chitosan composite hydrogel was immersed in 300 g of deionized water for 72 h.

[0021] Comparative Example 2 S1: 3 g acrylic acid, 2.5 mg N, N'-methylenebis(acrylamide), 10.87 mg 2,2'-azobis(2-methylpropionamidine) dihydrochloride, and 4.5 g MXene dispersion were added to 2.5 g deionized water and stirred to form a mixed solution; S2: The mixed solution was first subjected to ultrasonic treatment for 30 minutes and then vacuum stirred for 10 minutes to mix and degas; S3: injecting it into a mold consisting of two glass plates separated by a 1 mm silicone gasket; placing the mold in a constant temperature box at 50°C to allow acrylic acid to undergo free radical polymerization for 6 hours to generate a MXene / polyacrylic acid composite hydrogel; S4: At room temperature, the MXene / polyacrylic acid composite hydrogel was immersed in 300 g of 43% ammonium sulfate solution for 72 h.

[0022] Comparative Example 3 S1: 0.6 g chitosan, 3 g acrylic acid, 2.5 mg N, N'-methylenebis(acrylamide), and 10.87 mg 2,2'-azobis(2-methylpropionamidine) dihydrochloride were added to 7 g deionized water and stirred to form a mixed solution; S2: The mixed solution was first subjected to ultrasonic treatment for 30 minutes and then vacuum stirred for 10 minutes to mix and degas; S3: Inject the mixed solution into a mold consisting of two glass plates separated by a 1 mm silicone gasket; place the mold in a constant temperature box at 50° C. to allow acrylic acid to undergo free radical polymerization for 6 hours to generate polyacrylic acid-chitosan composite hydrogel.

[0023] S4: At room temperature, the polyacrylic acid-chitosan composite hydrogel was immersed in 300 g of 43% ammonium sulfate solution (salting out) for 72 h to obtain a strong polyacrylic acid-chitosan double network hydrogel.

[0024] Comparative Example 4 S1: 0.6 g chitosan, 3 g acrylic acid, 2.5 mg N,N'-methylenebis(acrylamide), and 10.87 mg 2,2'-azobis(2-methylpropionamidine) dihydrochloride were added to 7 g deionized water and stirred to form a mixed solution.

[0025] S2: The mixed solution was first subjected to ultrasonic treatment for 30 minutes and then mixed and degassed by vacuum stirring for 10 minutes.

[0026] S3: The mixed solution was injected into a mold consisting of two glass plates separated by a 1 mm silicone gasket. The mold was placed in a 50° C. thermostat to allow acrylic acid to undergo free radical polymerization for 6 hours to generate polyacrylic acid-chitosan composite hydrogel.

[0027] S4: The polyacrylic acid-chitosan composite hydrogel was immersed in 300 g of deionized water at room temperature for 72 h.

[0028] Example 1

[0029] S1: 0.6 g chitosan, 3 g acrylic acid, 2.5 mg N, N'-methylenebis(acrylamide), 10.87 mg 2,2'-azobis(2-methylpropionamidine) dihydrochloride, and 4.5 g MXene dispersion were added to 2.5 g deionized water and stirred to form a mixed solution; S2: The mixed solution was first subjected to ultrasonic treatment for 30 minutes and then vacuum stirred for 10 minutes to mix and degas; S3: injecting it into a mold consisting of two glass plates separated by a 1 mm silicone gasket; placing the mold in a constant temperature box at 50°C to allow acrylic acid to undergo free radical polymerization for 6 hours to generate a MXene polyacrylic acid-chitosan composite hydrogel; S4: At room temperature, the MXene / polyacrylic acid-chitosan composite hydrogel was immersed in 300 g of 43% ammonium sulfate solution (salting out) for 72 h to obtain a strong MXene / polyacrylic acid-chitosan double network hydrogel.

[0030] Example 2

[0031] The difference between Example 2 and Example 1 is that the amount of chitosan used in S1 is 0.4 g, and the other processes are the same as those in Example 1.

[0032] Example 3

[0033] The difference between Example 3 and Example 1 is that the amount of chitosan used in S1 is 0.2 g, and the other processes are the same as those in Example 1.

[0034] Example 4

[0035] The difference between Example 4 and Example 1 is that the concentration of the ammonium sulfate solution in S4 is 30%, and the other processes are the same as those in Example 1.

[0036] Example 5

[0037] The difference between Example 5 and Example 1 is that the concentration of the ammonium sulfate solution in S4 is 15%, and the other processes are the same as those in Example 1.

[0038] Example 6

[0039] The difference between Example 6 and Example 1 is that the amount of MXene dispersion used in S1 is 3 g, the amount of deionized water used is 4 g, and the other processes are the same as those in Example 1.

[0040] Example 7

[0041] The difference between Example 7 and Example 1 is that the amount of MXene dispersion used in S1 is 1.5 g, the amount of deionized water used is 5.5 g, and the other processes are the same as those in Example 1.

[0042] The preparation processes of all the examples herein are as follows Figure 1 shown.

[0043] Stress-strain curve test: The stress-strain curve test was performed on the hydrogels prepared in all the above-mentioned comparative examples 1, 2 and examples 1 to 5. The test results are as follows: Figure 2 shown. Figure 2 (a)~ Figure 2 (g) The test results of the hydrogels prepared by corresponding comparative example 1, example 1, example 2, example 3, comparative example 2, example 4 and example 5, respectively. Figure 2 (a)~ Figure 2 (d) It can be seen that since Comparative Example 1 does not contain chitosan, there is no molecular entanglement caused by the chitosan network and the Hofmeister effect, so it is the worst among Comparative Example 1 and Examples 1 to 3. Figure 2 (b)~ Figure 2 (d) It can be found that the increase of chitosan content can lead to the increase of chitosan network density, thus significantly improving the mechanical properties of hydrogel. Figure 2 (b) Figure 2 (e)~ Figure 2(g) It can be seen that the mechanical properties of the hydrogel prepared in Comparative Example 2 are obviously inferior to those of the hydrogels in Examples 1, 4, and 5 because there is no ammonium sulfate to induce the Hofmeister effect and double network formation, and as the concentration of ammonium sulfate increases, the mechanical properties of the hydrogel are significantly improved. Example 1 has the highest ammonium sulfate concentration and the highest chitosan content, so it has the highest degree of molecular entanglement and the highest chitosan network density, and thus exhibits the best mechanical properties.

[0044] Relative resistance change-strain curve test: The hydrogel prepared in Example 4 was made into a test strip with a length of 30 mm and a width of 6 mm, and a relative resistance-strain curve test was performed to measure the relative resistance change. Figure 3 As shown, the sensitivity of the test specimen in the strain range of 0-100% is 2.23, its sensitivity in the strain range of 100%-300% is 5.84, and its sensitivity in the strain range of 300%-500% is 11.66, and the linearity in this range is relatively high, which indicates that the hydrogel prepared by the present invention has good electrical properties of resistance-strain sensitivity.

[0045] Electromagnetic shielding performance test: The EMI SE values ​​of the hydrogel samples obtained in the THz band at a thickness of 1 mm for Comparative Example 2, Comparative Example 3, Comparative Example 4, Example 1, Example 4, Example 5, Example 6, and Example 7 were obtained using a terahertz time-domain spectroscopy (THz-TDS) test system (TAS7400TS). The THz-TDS test system is equipped with a temperature and humidity monitoring platform to eliminate the influence of water vapor on the measurement error. The temperature and humidity of the test environment were controlled below 5% RH. By setting the reflection and transmission modes, the power reflection, transmission, absorption coefficient, and EMI SE of the MXene / PAA-CS DN hydrogel were measured and analyzed. The relevant test data of the THz band were obtained according to the following equations (S1)-(S6). (S1) (S2) (S3) (S4) (S5) (S6) Among them, SE T , SE R and SE A It represents the overall shielding effectiveness, reflection and absorption efficiency (its unit is dB). And E s and E aIt refers to the terahertz pulse intensity passing through MXene / PAA-CS DN hydrogel and air in the transmission light path, E R and E i represents the incident and reflected THz pulse intensity of the hydrogel in the reflected light path, T p , T R , T A Represents power reflection, transmission, and absorption coefficients.

[0046] like Figure 4 As shown in (a), compared with the comparative example 2 without ammonium sulfate, the embodiments in the figure have a higher electromagnetic interference shielding effect (EMI SE), indicating that the introduction of ammonium sulfate is beneficial to improving the shielding effect of the hydrogel. Figure 4 As shown in (b), Comparative Example 3 has a lower EMI SE (~37.4dB) because it does not contain MXene, and as the MXene content in the examples increases, the EMI SE of the hydrogel is significantly improved. Obviously, the introduction of MXene helps to improve the electromagnetic shielding effect of the hydrogel. At the same time, Comparative Example 4, which does not contain MXene and ammonium sulfate, shows the lowest EMI SE (~27.5dB) among all comparative examples and examples, which is significantly lower than all examples containing MXene and ammonium sulfate. This further illustrates that the introduction of ammonium sulfate and MXene helps to improve the shielding effect of the hydrogel.

[0047] It should be noted that, in other embodiments, when the experimental process meets the following conditions, the purpose of the present invention can be achieved: The mass ratio of chitosan, acrylic acid, MXene dispersion and water is preferably (0.2-0.6):3:(1.5-4.5):(5.5-2.5), specifically 0.2:3:4.5:2.5, 0.6:3:1.5:5.5 or 0.6:3:3:4.

[0048] As for the temperature and time of the free radical polymerization reaction, the temperature is preferably 50° C. to 65° C., and the time is preferably 6 to 12 hours.

[0049] The concentration of the ammonium sulfate solution is preferably 15-43%, specifically 15%, 30% or 43%.

[0050] The mass ratio of the ammonium sulfate solution to the acrylic acid is preferably (200-1000):10, and specifically may be 200:10, 300:10 or 1000:10.

[0051] The soaking and salting-out time is preferably 48 h to 72 h, and specifically can be 48 h or 72 h.

[0052] Those skilled in the art can make appropriate selections of the above process parameters according to actual needs, and all of them can achieve the purpose of the present invention.

[0053] Obviously, the described embodiments are only some embodiments of the present invention, but not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing a strong electromagnetic interference shielding hydrogel material, characterized in that: The steps include: S1: adding chitosan, acrylic acid, crosslinking agent, thermal initiator and MXene dispersion into water to obtain a mixed solution; S2: subjecting the mixed solution to ultrasonic dispersion treatment, and then mixing it evenly in a vacuum environment and degassing it to obtain a reaction solution; S3: heating the reaction solution to thermally polymerize the acrylic acid therein to generate a MXene / polyacrylic acid-chitosan composite hydrogel; S4: The composite hydrogel is placed in an ammonium sulfate solution for salting out and soaking to obtain a strong electromagnetic interference shielding hydrogel material.

2. The method for preparing a tough electromagnetic interference shielding hydrogel material according to claim 1, characterized in that: The mass ratio of chitosan, acrylic acid, MXene dispersion and water in S1 is (0.2~0.6):3:(1.5~4.5):(5.5~2.5).

3. The method for preparing a tough electromagnetic interference shielding hydrogel material according to claim 1, characterized in that: The cross-linking agent in S1 is N,N'-methylenebis(acrylamide), and the thermal initiator is 2,2'-azobis(2-methylpropionamidine) dihydrochloride.

4. The method for preparing a tough electromagnetic interference shielding hydrogel material according to claim 1, characterized in that: The concentration of the MXene dispersion is 20 mg / mL, and the flake size of the MXene is between 200 and 500 nm.

5. The method for preparing a strong electromagnetic interference shielding hydrogel material according to claim 1, characterized in that: The heating temperature in S3 is 50° C. to 65° C., and the heating time is 3 to 10 hours.

6. The method for preparing a tough electromagnetic interference shielding hydrogel material according to claim 1, characterized in that: The concentration of the ammonium sulfate solution in S4 is 15%~43%, and the mass ratio of the ammonium sulfate solution to the MXene / polyacrylic acid-chitosan composite hydrogel is (200~1000):

10.

7. The method for preparing a strong electromagnetic interference shielding hydrogel material according to claim 1, characterized in that: The temperature of the ammonium sulfate in S4 is 0°C to 30°C; the salting-out time is 48h to 72h.

8. A strong electromagnetic interference shielding hydrogel material, characterized in that: The invention discloses a novel novel nanostructured carbon foam prepared by the preparation method described in any one of claims 1 to 7.

9. The strong electromagnetic interference shielding hydrogel material as described in claim 8 is used to prepare flexible electromagnetic shielding devices and flexible sensors.

Citation Information

Patent Citations

  • Tough magnetic conductive hydrogel material as well as preparation method and application thereof

    CN115785483A

  • Self-adhesive MXene-based electromagnetic shielding hydrogel as well as preparation method and application thereof

    CN117624478A

Cited By

  • Cold atmospheric pressure plasma modified electromagnetic interference shielding hydrogel material

    CN121895505A